SigE: A master regulator of Mycobacterium tuberculosis - Manganelli, Riccardo; Cioetto-Mazzabò, Laura; Segafreddo, Greta; Boldrin, Francesca; Sorze, Davide; Conflitti, Marta; Serafini, Agnese; Provvedi, Roberta (Frontiers in Microbiology, 2023)
The Extracellular function (ECF) sigma factor SigE is one of the best characterized out of the 13 sigma factors encoded in the Mycobacterium tuberculosis chromosome. SigE is required for blocking phagosome maturation and full virulence in both mice and guinea pigs. Moreover, it is involved in the response to several environmental stresses as surface stress, oxidative stress, acidic pH, and phosphate starvation. Underscoring its importance in M. tuberculosis physiology, SigE is subjected to a very complex regulatory system: depending on the environmental conditions, its expression is regulated by three different sigma factors (SigA, SigE and SigH) and a two-component system (MprAB). SigE is also regulated at the post-translational level by an anti-sigma factor (RseA) which is regulated by the intracellular redox potential and by proteolysis following phosphorylation from PknB upon surface stress. The set of genes under its direct control includes other regulators, as SigB, ClgR, and MprAB, and genes involved in surface remodelling and stabilization. Recently SigE has been shown to interact with PhoP to activate a subset of genes in conditions of acidic pH. The complex structure of its regulatory network has been suggested to result in a bistable switch leading to the development of heterogeneous bacterial populations. This hypothesis has been recently reinforced by the finding of its involvement in the development of persister cells able to survive to the killing activity of several drugs.